The illustrated man - Bradbury, Ray, 1920- (New York : Bantam, 1982)
Eighteen science fiction stories, including "The Other Foot", "Zero Hour," "The Long Rain," "Rocket Man," "The Last Night of the World," and "The Exiles.".
Wilson's Fiction.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Science fiction; Short stories; Science fiction; Short stories